FDI inflows and economic growth in north African countries: Do institutional quality and financial development matter? - Yahyaoui, Abdelkarim (Asian Economic and Financial Review, 2025)
Our study enhances the existing literature regarding the relationship between foreign direct investment (FDI) and economic growth. Our objective is to identify the main transmission mechanisms through which FDI flows can stimulate economic growth in North African countries. An analysis of four North African countries (Tunisia, Algeria, Morocco, and Egypt) from 2000 to 2022 clearly shows that FDI flows are positively related to economic growth, and this relationship improves when these countries have strong institutions and a better financial system. We obtained the results using the Generalized Method of Moments Estimation (System GMM). Our main findings indicate that the quality of institutions and a well-developed financial system are key factors in attracting foreign direct investment (FDI). Therefore, the successful implementation of the rule of law attracts foreign investment, promoting economic growth. Elevated levels of corruption diminish the beneficial impact of FDI on economic growth in these nations. To attract foreign investment, these countries need a robust system with low corruption, a functioning legal system, and fewer bureaucratic obstacles. The results of this study have significant implications for policymakers. Our study provides recommendations for policymakers in North African nations based on the obtained results.